Dalbavancin in the treatment of skin and soft tissue infections - Nikulin A.A. (Клиническая микробиология и антимикробная химиотерапия, 2018)
Dalbavancin is a semi-synthetic lipoglycopeptide registered for the treatment of acute bacterial skin and skin structure infections caused by Gram-positive microorganisms, including MRSA. It has a prolonged half-life and excellent tissue levels which allows to its once-weekly administration. Article reviews data of in vitro, in vivo studies and clinical trials results, as well as potential indications of dalbavancin.